Resisting the pregnant pediatrician - MacKay, Sue (Susan) (Harlequin medical romance, 2023)
To escape a recent trauma, famous ER doc Aaron takes up a residency in Italy. His plan? Keep a low profile and enjoy his anonymity in a sleepy little village. Meeting gorgeous pediatrician Bella is not on the agenda! But widowed Bella is pregnant, so despite their undeniable attraction, Aaron's determined to put her firmly in the friend zone. Until the night their desire becomes too intense to resist!